A STUDY OF THE INFLUENCE OF SERVICE QUALITY, PERCEIVED VALUE, TRUST, AND PRICE ON DELIVERY SERVICES ON ONLINE CUSTOMER LOYALTY - Zana Cobhita Arethusa Siswanto; Elevita Yuliati (SEAN Institute, 2023)
The use of e-commerce sites has increased rapidly. This also increases the use of expedition services as a carrier for the mobility of goods from the hands of the seller to the hands of the buyer. Considering the important role that shipping services have, more and more shipping service businesses are emerging and competing to maintain their existence. To improve previous research, this study presents a discussion of the effect of the service quality, perceived value, trust, and price variables provided by the expedition service on the emergence of customer satisfaction and customer loyalty. This study analyzed primary data from 217 respondents obtained through the distribution of online questionnaires and observed the effect of each variable using the PLS-SEM analysis method. It was found that service quality, perceived value, trust, and price had a significant effect on customer satisfaction and loyalty. Then, trust is able to mediate service quality and perceived value in a positive way toward customer satisfaction.